Involvement of Neuro-Immune Interactions in Pruritus With Special Focus on Receptor Expressions - Ruppenstein, Aylin; Limberg, Maren M.; Loser, Karin; Kremer, Andreas E.; Homey, Bernhard; Raap, Ulrike (Frontiers in Medicine, 2021)
Pruritus is a common, but very challenging symptom with a wide diversity of underlying causes like dermatological, systemic, neurological and psychiatric diseases. In dermatology, pruritus is the most frequent symptom both in its acute and chronic form (over 6 weeks in duration). Treatment of chronic pruritus often remains challenging. Affected patients who suffer from moderate to severe pruritus have a significantly reduced quality of life. The underlying physiology of pruritus is very complex, involving a diverse network of components in the skin including resident cells such as keratinocytes and sensory neurons as well as transiently infiltrating cells such as certain immune cells. Previous research has established that there is a significant crosstalk among the stratum corneum, nerve fibers and various immune cells, such as keratinocytes, T cells, basophils, eosinophils and mast cells. In this regard, interactions between receptors on cutaneous and spinal neurons or on different immune cells play an important role in the processing of signals which are important for the transmission of pruritus. In this review, we discuss the role of various receptors involved in pruritus and inflammation, such as TRPV1 and TRPA1, IL-31RA and OSMR, TSLPR, PAR-2, NK1R, H1R and H4R, MRGPRs as well as TrkA, with a focus on interaction between nerve fibers and different immune cells. Emerging evidence shows that neuro-immune interactions play a pivotal role in mediating pruritus-associated inflammatory skin diseases such as atopic dermatitis, psoriasis or chronic spontaneous urticaria. Targeting these bidirectional neuro-immune interactions and the involved pruritus-specific receptors is likely to contribute to novel insights into the underlying pathogenesis and targeted treatment options of pruritus.